Management of symptomatic patients with suspected mild-moderate COVID-19 in general practice. What was published within the first year of the pandemic? A scoping review. Issue 1 (1st January 2021) - Holm, Anne; Møller, Anne; Aabenhus, Rune
Abstract: Background: Most COVID-19 patients experience a mild course of the disease and can be managed in general practice. However, in the early pandemic, most research was conducted in secondary care. Objectives: This scoping review aimed to identify original research published within the first year of the pandemic relevant to general practice regarding symptomatic, non-hospitalised patients with mild to moderate COVID-19 disease to provide an overview of published research. Methods: PubMed was searched for studies written in English, Swedish, Danish, or Norwegian published before 1 April 2021. Two authors screened all titles and abstracts and identified full texts. Results: We screened 1303 titles and abstracts and retrieved 128 full texts. An additional 44 full-texts were obtained from references. After full-text reading, 79 articles were included, six of which were conducted in general practice, 20 in the community, 42 in hospitals, and 11 in other settings. Therapy and harm were investigated in randomised controlled trials in 11 out of 17 studies; the diagnosis was investigated using a diagnostic accuracy design in four out of 26 studies and prognosis in prospective studies in 10 out of 21 studies. The remaining 15 studies had other research questions. Conclusion: Although general practitioners in most countries must have been involved in managing patients with COVID-19, little research has been published from general practice during the first year of the pandemic. General practice research environments must be able to respond quickly in case of future pandemics.